2014
DOI: 10.1186/2193-1801-3-389
|View full text |Cite
|
Sign up to set email alerts
|

Effects of combined netupitant and palonosetron (NEPA), a cancer supportive care antiemetic, on the ECG of healthy subjects: an ICH E14 thorough QT trial

Abstract: Chemotherapy-induced nausea and vomiting is ranked among the worst side effects of chemotherapy. NEPA is an oral fixed-dose combination antiemetic under development, consisting of netupitant 300 mg, a highly selective NK1 receptor antagonist (RA), and palonosetron 0.5 mg, a pharmacologically and clinically distinct 5-HT3 RA. Although palonosetron is not associated with relevant ECG effects, this study evaluated cardiovascular safety of netupitant in combination with palonosetron, as well as its tolerability.Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 35 publications
0
25
0
2
Order By: Relevance
“…In addition, as the cardiac safety of NEPA has been carefully evaluated previously, ECG assessments were not included in the current trial. Prior cardiac safety evaluations for NEPA have included a thorough QTc study , the oral NEPA phase III study in the AC setting , and the prior IV NEPA study in the cisplatin setting . Previously, there were no cardiac safety concerns based on ECGs observed with either IV or oral NEPA formulations during initial or repeated cycles in >1,500 patients participating in phase III studies.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, as the cardiac safety of NEPA has been carefully evaluated previously, ECG assessments were not included in the current trial. Prior cardiac safety evaluations for NEPA have included a thorough QTc study , the oral NEPA phase III study in the AC setting , and the prior IV NEPA study in the cisplatin setting . Previously, there were no cardiac safety concerns based on ECGs observed with either IV or oral NEPA formulations during initial or repeated cycles in >1,500 patients participating in phase III studies.…”
Section: Discussionmentioning
confidence: 99%
“…In healthy subjects, no medically relevant changes in heart rhythm, pulse rate, individual heart rate-corrected QT interval, QRS interval, or cardiac morphology were observed for NEPA in a randomized, placebo-and positively controlled study conducted in 197 healthy subjects. 27 In addition, a phase 3 study in cancer patients receiving MEC showed no increased cardiac safety concern when patients received NEPA instead of palonosetron alone. 34 In line with these data, no medically relevant changes in ECG parameters and only slight decreases in blood pressure were observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously demonstrated that these netupitant metabolites are pharmacologically active. 27,28 The bioanalysis of the obtained plasma samples was conducted in accordance with the Organisation for Economic Co-operation and Development Principles of Good Laboratory Practice. Palonosetron and netupitant and its metabolites (M1, M2, and M3) were determined using 2 fully validated liquid chromatography-tandem mass spectrometry (LC-MS/MS) methods with stable isotope-labeled internal standards.…”
Section: Assessmentsmentioning
confidence: 99%
“…20 Between-subject variability is between 42% and 56% for netupitant 200 to 600 mg and between 20% and 29% for palonosetron 0.5 to 1.5 mg. 20 At the doses studied, netupitant and palonosetron have no effect on the pharmacokinetic parameters of each other. 1,21 Following oral administration of netupitant and palonosetron in healthy subjects, the time to maximum concentration (T max ) is about 5 hours for both drugs.…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…1 A placebo-controlled QTc study showed that doses ranging from netupitant 200 mg/palonosetron 0.5 mg to netupitant 600 mg/palonosetron 1.5 mg did not clinically increase the QTc interval compared with placebo. 1,20 Netupitant is classified as Pregnancy Category C; no adequate and well-controlled studies have been performed in pregnant women. Netupitant/palonosetron should only be used in pregnancy if the benefits clearly outweigh the risks.…”
Section: Warnings and Precautionsmentioning
confidence: 99%